ANALISIS KEBIJAKAN POLITIK HUKUM DALAM PENEGAKAN TINDAK PIDANA KORUPSI MELALUI PENGESAHAN RANCANGAN UNDANG-UNDANG PERAMPASAN ASET - Ira, Lisa; Sitorus, Yeni Lisa; Erdawati, Lidya; Nababan , Veronika Laurensia Yolanda Br; Haryanti, Dewi (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Corruption is an extraordinary crime that should be eradicated. The increase in corruption cases is still stagnant despite various efforts to reduce the number of corruptions. As a country that has ratified the United Nations Convention Against Corruption (UNCAC) through Law No. 7/2006 on the Ratification of the UN Convention Against Corruption, Indonesia should have the same legal standing in matters regulated in UNCAC, including the issue of confiscation of criminal proceeds. The main objective of the Asset Forfeiture Law is how to recover state losses (asset recovery), so that the losses suffered by the state are not significant. This research is conducted to examine and discuss the influence of legal politics in combating corruption through the establishment of the Asset Forfeiture Bill. The research method used in this research is normative juridical, by analyzing applicable legal norms supported by doctrines that develop in law. The results showed that legal politics influenced the ratification of the Asset Forfeiture Bill. The Asset Forfeiture Bill is important to be ratified immediately in order to provide a deterrent effect for corruptors